ACTUAL PROBLEMS OF DEVELOPMENT OF SMART CITIES - SEVASTYANOV, RUSLAN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the development of the "smart city". This topic is important to ensure the effective functioning of modern cities and take into account the needs of their inhabitants. Smart City is an innovative system. This system uses sensors, internet of things (IoT), networks, big data to increase the competitiveness and efficiency of urban services. It is established that the sustainable development of a "smart city" must take into account economic, social and environmental aspects and ensure its compliance with the needs of present and future generations. The development of "smart cities" involves the integration and coordination of services in cities. Such development should provide opportunities for remote participation of citizens in city management. Strategic directions of Zaporizhzhya city development are considered. The development strategy of Zaporizhzhya until 2028 provides for the development of a healthy environment, resource conservation, promotion of entrepreneurship, creative economy, improving the quality of life. In Zaporizhzhya, the main goals of the development of a "smart city" are to increase the share of waste processing, reduce air pollution in the city, reduce water use by industrial enterprises. The sphere of entrepreneurship and creative economy envisages the development of processing industries and logistics with low technogenic impact on the environment, reduction of emissions and introduction of ecological technologies. For the development of the creative economy of Zaporizhzhya, gradual commercialization of science, holding of art projects and festivals, increase of coworking and popularization of IT-technologies are envisaged. The article systematizes electronic smart services in Zaporizhzhya. In particular, the city is developing electronic smart services to improve the further comfort of citizens ("EasyWay", "Waze" and others). The development of smart city services in Zaporizhzhya covers the areas of transport, housing and communal services, health and medicine, cultural and entertainment, socio-economic and administrative-social services. Such actions help to accelerate management decisions, save budget funds, improve the provision of information services for citizens and businesses.